1966
DOI: 10.1002/bit.260080306
|View full text |Cite
|
Sign up to set email alerts
|

Aeration of concentrated activated sludge

Abstract: SummaryA multiphase project has been planned to develop a new biological process capable of economically treating high BOD wastes. Herein is presented the results of the first phase of the program, in which the feasibility of growing concentrated microbial cultures was investigated and the oxygen and power requirements for maintaining such cultures were determined. An example is given of the sc:ile-up of power requirements for oxygen transfer in a protot,ype system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1968
1968
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Essentially, the MBR configuration of AS combine the aeration tank of the AS process with a membrane filtration module. Research on the subject was first initiated in 1962 . However, it took more than 20 years to further expand experimental data for developing the MBR system as it is conceived today, when a membrane module was first submerged into the aeration tank in 1989 .…”
Section: Reshaping the Processmentioning
confidence: 99%
“…Essentially, the MBR configuration of AS combine the aeration tank of the AS process with a membrane filtration module. Research on the subject was first initiated in 1962 . However, it took more than 20 years to further expand experimental data for developing the MBR system as it is conceived today, when a membrane module was first submerged into the aeration tank in 1989 .…”
Section: Reshaping the Processmentioning
confidence: 99%
“…Preliminary studies performed by Stiefel,et.al.,(16) reported that wastes with biochemical oxygen demands (BOD) ranging up to 10,000 mg/1 could be successfully treated by maintaining a MLVSS level of 25,000 mg/1 in an aerator. Other advantages of keeping a high MLSS or MLVSS in an aerator will be discussed later.…”
Section: Basic Considerationsmentioning
confidence: 99%
“…It was previously mentioned that an activated sludge process having a high concentration of MLVSS could effectively treat wastes with a high BOD concentration (13) (16). The use of pure oxygen would make this more theoretically acceptable (27) (28)…”
Section: Organismsmentioning
confidence: 99%